2011
DOI: 10.1002/mrc.2758
|View full text |Cite
|
Sign up to set email alerts
|

NQR study of chalcogenide glasses Ge‐As‐Se

Abstract: A three-component Ge-As-Se system is studied by the nuclear quadrupole resonance (NQR) method on (75)As nuclei and by the nutation NQR spectroscopy. The NQR (75)As spectra of the glasses Ge(0.021) As(0.375) Se(0.604), Ge(0.043) As(0.348) Se(0.609) and Ge(0.068) As(0.318) Se(0.614) reveal broad lines with two peaks assigned to the main structural unit of As(2)Se(3). With increasing average coordination number ( ̅r), the spectrum signals are shifted towards higher frequencies. At ̅r > 2.54, the spectrum becomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 14 publications
(19 reference statements)
0
14
0
Order By: Relevance
“…leading to effects of the formation of clusters. The 75 As NQR spectra and their frequencies and linewidths for chalcogenide semiconductors of Ge-AsSe different compositions are presented in our previous work [9]. The results of our study of the NQR spectra for the samples of this system show that changing their chemical composition leads to significant differences in the NQR spectra.…”
Section: The Previous Nqr and Epr Study Of Ge-as-se And As-sb-se Glasmentioning
confidence: 53%
See 2 more Smart Citations
“…leading to effects of the formation of clusters. The 75 As NQR spectra and their frequencies and linewidths for chalcogenide semiconductors of Ge-AsSe different compositions are presented in our previous work [9]. The results of our study of the NQR spectra for the samples of this system show that changing their chemical composition leads to significant differences in the NQR spectra.…”
Section: The Previous Nqr and Epr Study Of Ge-as-se And As-sb-se Glasmentioning
confidence: 53%
“…It has been found that function η (¯ ), exhibits a maximum at r = 2.425 which probably indicates a change in the glass structure. Table 2 shows the frequency and width of NQR 75 As in Ge-As-Se glasses (T = 77 K) from the works [6,9]. Fig.…”
Section: The Interpretation Of the Experimental Results Of The Cgs Stmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of NQR to study disordered systems, in particular glassy semiconductors, is based on the relation between their structure and the distribution of magnitudes of the electric field gradient (EFG) at the quadrupolar nuclei. Applying new research methods in the NQR spectroscopy [on the basis of the spin echo signal theory for very wide NQR lines and on examining the geometrical phase (Berry phases) of NQR signals] to determine the asymmetry parameter of the EFG in the examined semiconductors allowed much information to be obtained in relation to the local structure of these compounds …”
Section: Introductionmentioning
confidence: 99%
“…Recently nuclear quadrupole resonance (NQR) spectroscopy has been employed to study the structure of disordered solids [1][2][3][4][5][6]. A second spectroscopic method that has been used for the same goal is the electron paramagnetic resonance * E-mail: glotova@amu.edu.pl (EPR) spectroscopy [7].…”
Section: Introductionmentioning
confidence: 99%